The Role of Artificial Intelligence in Improving the Effectiveness and Transparency of Public Services in Makassar City - Zainal, Henni; Mahmud, Muh Nasir (Universitas Negeri Makassar, 2026)
Digital transformation has become a strategic agenda for local governments to improve the quality of effective, efficient, and transparent public services. One technology that has great potential in supporting this agenda is Artificial Intelligence (AI). The application of AI in public services enables faster, more accurate, and more responsive service processes to community needs, while minimizing maladministration practices. This study aims to analyze the role of Artificial Intelligence in improving the effectiveness and transparency of public services in Makassar City, as well as identifying opportunities and challenges for its implementation in the context of local government. The research method used is a qualitative approach with a descriptive-analytical design. Data collection techniques were carried out through in-depth interviews with local government officials, digital service system managers, and public service users, and supported by documentation studies of policies, performance reports, and digital-based public service application systems implemented in Makassar City. Data analysis was carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that the use of Artificial Intelligence in public services in Makassar City plays a significant role in increasing service effectiveness, especially in aspects of service speed, decision-making accuracy, and improving the quality of interaction between the government and the community. In addition, AI also contributes to increasing service transparency through service tracking systems, information automation, and more accountable and real-time data management. However, this study also found several challenges in AI implementation, including limited human resource capacity, digital infrastructure readiness, data integration between agencies, and issues of ethics and personal data protection. This study concluded that Artificial Intelligence has a strategic role in supporting bureaucratic reform and good governance in Makassar City. Therefore, a comprehensive policy strategy, strengthening the capacity of the apparatus, and multi-stakeholder collaboration are needed to ensure the implementation of AI is sustainable, inclusive, and oriented towards the public interest.